Rapid evolution of magnetic decreases (MDs) and discontinuities in the solar wind: ACE and Cluster - Tsurutani, B.T.; Guarnieri, F.L.; Lakhina, G.S.; Hada, Tohru (My University, 2005)
[1] An experiment was conducted to identify and measure the same magnetic decreases (MDs) and interplanetary discontinuities at two different points in space separated by ∼0.01 AU along the radial distance from the sun. The ACE and Cluster satellite data were used in this study. Solar wind speeds measured at Cluster were used to calculate the approximate (earlier) times of arrival at ACE. The field component changes at both spacecraft were intercompared to ensure that the same discontinuities were detected. Out of 7 MDs/discontinuities selected, 6 were identified at ACE. The MDs/discontinuities were identified within 7 s to 35 s of the convection times. The MD thicknesses at Cluster were substantially smaller than at ACE. The ratio of thicknesses varied from 0.21 to 0.045. One possible interpretation of this observation is that the Alfvén wave front (rotational discontinuity) is steepening by a factor of greater than 15 per wavelength propagated. This may have important consequences for the generation of high frequency turbulence in interplanetary space. It is noted that the 6 discontinuities transited the ∼0.01 AU distance from ACE to Cluster with essentially the solar wind convection speed. A possible mechanism contributing to this feature is discussed.
Keywords: Magnetic decreases (MDs); Solar wind; Cluster; Alfvén wave; ACE